2008
DOI: 10.1002/ejoc.200700717
|View full text |Cite
|
Sign up to set email alerts
|

“Furan Endwise Peeling” of Celluloses: Mechanistic Studies and Application Perspectives of a Novel Reaction

Abstract: The mechanism of a novel reaction type, the “furan endwise peeling” reaction, has been studied. Making extensive use of experiments on model compounds, the structural prerequisites to the reaction were found to be a 2‐hydroxpyran β‐glycosidically linked to a 2‐(2‐furyl)ethyl moiety. Proceeding from the reducing end of the celluloses, the reaction causes the one‐by‐one loss of anhydroglucose units (AGUs) which are concomitantly converted into 2‐(tetrahydroxybutyl)furans (4) by co‐reacting with 1,3‐dicarbonyl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…High acylation efficiencies showed that the dioxane‐based activation represents an excellent alternative to the established methods. In addition, it leads to clear and colorless cellulose solutions, as opposed to those prepared using the thermal activation, where at least a small extent of degradation is likely to take place, resulting in yellowish or amber solutions 29, 40–42. A detailed discussion of the use of dioxane‐based activation method in the dissolution of different cellulose pulps, physicochemical analysis of the activated samples, and comments on the activation mechanism will be the subject of a forthcoming separate report.…”
Section: Resultsmentioning
confidence: 99%
“…High acylation efficiencies showed that the dioxane‐based activation represents an excellent alternative to the established methods. In addition, it leads to clear and colorless cellulose solutions, as opposed to those prepared using the thermal activation, where at least a small extent of degradation is likely to take place, resulting in yellowish or amber solutions 29, 40–42. A detailed discussion of the use of dioxane‐based activation method in the dissolution of different cellulose pulps, physicochemical analysis of the activated samples, and comments on the activation mechanism will be the subject of a forthcoming separate report.…”
Section: Resultsmentioning
confidence: 99%
“…2‐Phenylethyl β‐ D ‐glucopyranoside: 41 1 H NMR (CD 3 OD): δ =2.941 (1 H, m, Σ J =25.0 Hz, H‐2′u), 2.973 (1 H, m, Σ J =25.0 Hz, H‐2′d), 3.205 (1 H, dd, J =9.2, 7.8 Hz, H‐2), 3.286 (1 H, m, H‐5), 3.305 (1 H, m, H‐4), 3.369 (1 H, dd, J =9.2, 8.6 Hz, H‐3), 3.684 (1 H, dd, J =11.9, 5.5 Hz, H‐6u), 3.779 (1 H, ddd, J =9.7, 8.2, 6.7 Hz, H‐1′u), 3.882 (1 H, dd, J =11.9, 2.1 Hz, H‐6d), 4.111 (1 H, ddd, J =9.7, 8.2, 6.8 Hz, H‐1′d), 4.322 (1 H, d, J =7.8 Hz, H‐1), 7.197 (1 H, m, H‐ para ), 7.267 (4 H, m, H‐ ortho , H‐ meta ); 13 C NMR (CD 3 OD): δ =37.53 (C‐2′), 63.05 (C‐6), 71.94 (C‐4), 72.01 (C‐1′), 75.40 (C‐2), 78.26 (C‐5), 78.40 (C‐3), 104.68 (C‐1), 127.50 (C‐ para ), 129.64 (C‐ meta ), 130.32 (C‐ ortho ), 140.36 (C‐ ipso ); MS (ESI): m/z =307.1152 [M+Na] + , calcd. mass for C 14 H 20 O 6 Na: 307.1152.…”
Section: Methodsmentioning
confidence: 99%
“…3) In this paper, seven new saponins (1-4, 6-8) and a new lignan glucoside (14) were isolated from the extract of C. barbinervis, together with echinocystic acid 3-β-d-glucuronopyranoside (5), 4) hemsganoside B (9), 5,6) scheffleraside II (10), 5) rotundic acid (11), 7) barbinervic acid (12), 8) clethric acid (13), 9,10) 8-O-4′ neolignan 7-O-β-glucopyranoside (15), 11) rourinoside (16), 12) epicatechin (17), 13) pavetannin A (18), 14) 2-phenylethyl β-glucopyranoside (19), 15) 2-phenylethyl O-α-larabinofuranosyl-(1→ 6)-β-d-glucopyranoside (20), 16) 2-phenylethyl O-α-l-rhamnopyranosyl-(1→ 6)-β-d-glucopyranoside (21), 17) and methyl salicylate β-primeveroside (22) 18) (Figs. 1, 2).…”
mentioning
confidence: 99%
“…Fractions 2A (90.1%, 2.0 mg/mL), 2C (68.0%, 2.0 mg/mL), 2D (78.9%, 2.0 mg/mL), and 2E (71.7%, 2.0 mg/mL) separated from 1C (91.4%, 2.0 mg/mL) had high inhibitory activities. Nine constituents (14)(15)(16)(17)(18)(19)(20)(21)(22) were isolated from 2A, and 17 was active (IC 50 0.94 mm). Catechins are already known to have hyaluronidase inhibitory activity.…”
mentioning
confidence: 99%